A REQUIREMENTS ANALYSIS OF INQURY MODEL DEVELOPMENT BASED ON SCIENCE, ENVIRONMENT, TECHNOLOGY, SOCIETY (SETS) - Juhairiah Juhairiah; Elsje Theodora; Herliani Herliani (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2021)
Problems that occur that students' critical thinking skills are currently lacking so that many students do not apply concepts in everyday life, so it is very necessary to conduct a needs analysis related to the tools used by the teacher and the approach used by the teacher. The purpose of this study is to find out what problems are faced by teachers when developing learning tools based on the indicators that exist in each device. This research method is a percentage and descriptive data collection technique using research instruments in the form of a questionnaire filled by respondents will be analyzed quantitatively (Percentage) and descriptive (Qualitative). The results showed that 80% of teachers did not understand how to develop inquiry learning tools and use the SETS approach. So it can be concluded that the development of learning tools needs to be implemented to improve student's critical thinking skills.